Evolution of cytochrome P450 gene superfamily in different cellular organisms - Shi, Yuxia; Zong, Shu; Zhang, Hejian; Liu, Shuo; Yang, Junru; Lu, Lina; Liu, Xiaonan; Cheng, Jian; Jiang, Huifeng (Frontiers in Ecology and Evolution, 2026)
Cytochrome P450 enzymes, a widespread monooxygenase superfamily, are crucial for metabolic diversity and environmental adaptation. However, systematic analysis and comparison of the expansion of the P450 gene superfamily and its potential mechanisms in different biological groups remains limited. Here, we analyzed one million P450 gene sequences from Viridiplantae, Metazoa, Fungi, and Bacteria by integrating protein language models, phylogenetic inference, and gene duplication pattern analysis to resolve their evolutionary trajectories. Our results show that P450 genes expanded primarily through vertical inheritance, but 24 potential cross-group horizontal gene transfer events were also detected. Ecological analyses suggest a potential link between P450 expansion and the complexity of terrestrial niches: P450s are abundant in Viridiplantae and Fungi, with large-scale expansions in Metazoa and Bacteria restricted to specific lineages. Comparative duplication analyses highlight distinct group-specific mechanisms: Viridiplantae are driven by synergistic whole-genome duplication and tandem duplication; Metazoa expand mainly via tandem duplication, facilitating rapid functional diversification; Fungi rely predominantly on dispersed duplication, enhancing metabolic plasticity; and Bacteria maintain their ability to survive under environmental stress by dispersed duplication. At the family level, we identified three typical expansion patterns: high coverage with low copy number (e.g., CYP51), high coverage with high copy number (e.g., CYP71), and low coverage with high copy number (e.g., CYP725). These patterns collectively support core, secondary, and specialized metabolic functions in different biological groups. This study reveals the expansion patterns and driving factors of the P450 gene superfamily across biological groups, offering new genomic insights into its evolutionary diversification.